Nicodemites: faith and concealment between Italy and Tudor England - Overell, M. Anne (St Andrews studies in reformation history, 2019)
In Nicodemites: Faith and Concealment Between Italy and Tudor England, Anne Overell examines a rarely glimpsed aspect of sixteenth-century religious strife: the thinkers, clerics and rulers who concealed their faith. This work goes beyond recent scholarly interest in conformity to probe inward dilemmas and the spiritual and cultural meanings of pretence. Among the dissimulators who appear here are Cardinal Reginald Pole and his circle in Italy and in England, and also John Cheke and William Cecil. Although Protestant and Catholic polemicists condemned all Nicodemites, most of them survived reformation violence, while their habits of silence and secrecy became influential. This study concludes that widespread evasion about religious belief contributed to the erratic development of toleration